Advances in systemic therapy for the first-line treatment of unresectable HCC. Issue 6 (3rd June 2021) - Vogel, Arndt; Bathon, Melanie; Saborowski, Anna
ABSTRACT: Introduction : Hepatocellular carcinoma (HCC) is one of the most common and deadliest cancers worldwide. In recent years, several drugs have been approved in first- and second-line setting. Currently, several phase-III trials are ongoing with combinations of checkpoint inhibitors, tyrosine kinase inhibitors (TKI) and anti-angiogenic antibodies, which will most likely increase therapeutic options in frontline therapy in the near future. Areas covered : This review summarizes the standard of care in first-line systemic therapy for patients with advanced HCC and provides an outlook on the most promising combinations currently tested in prospective trials. Expert opinion : The recent approval of novel substances has substantially changed the field of palliative treatment strategies in patients with advanced HCC. Immuno-oncology (IO)-based combination therapies will become the next standard of care in frontline HCC. The potent anti-tumor efficacy and good tolerability of these therapies will increase the use of upfront systemic therapy in patients with intermediate stage HCC.